2016
DOI: 10.1387/ijdb.160045mo
|View full text |Cite
|
Sign up to set email alerts
|

Platelet derived growth factor B gene expression in the Xenopus laevis developing central nervous system

Abstract: Platelet-derived growth factor B (PDGF-B) belongs to the mitogen and growth factor family and like the other members it has many roles in cell differentiation, proliferation and migration during development, adult life and in pathological conditions. Among them it has been observed that aberrant PDGF signalling is frequently linked to glioma development and progression, and Pdgf-b over-expression in mouse neural progenitors leads to the formation of gliomas. Despite this evidence, the mechanisms underlying PDG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Following initiation of the epithelial-to-mesenchymal transition, migrating NCCs chemotax toward PDGF-A ligand in the surrounding tissue, resulting in directional migration (Bahm et al, 2017). The ligand pdgfb is also expressed in tissues adjacent to migrating NCCs in Xenopus embryos (Giannetti et al, 2016) and knock-down of this ligand results in impaired cNCC migration and defective development of the craniofacial cartilages and cranial nerves in a subset of morpholino-injected embryos (Corsinovi et al, 2019). In zebrafish, pdgfra is similarly expressed by pre-migratory and migratory cNCCs, while its ligand pdgfaa is correspondingly expressed at early stages in the midbrain and later in the oral ectoderm (Eberhart et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Following initiation of the epithelial-to-mesenchymal transition, migrating NCCs chemotax toward PDGF-A ligand in the surrounding tissue, resulting in directional migration (Bahm et al, 2017). The ligand pdgfb is also expressed in tissues adjacent to migrating NCCs in Xenopus embryos (Giannetti et al, 2016) and knock-down of this ligand results in impaired cNCC migration and defective development of the craniofacial cartilages and cranial nerves in a subset of morpholino-injected embryos (Corsinovi et al, 2019). In zebrafish, pdgfra is similarly expressed by pre-migratory and migratory cNCCs, while its ligand pdgfaa is correspondingly expressed at early stages in the midbrain and later in the oral ectoderm (Eberhart et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A new hint emerged from our recent analysis of the pdgf-b gene-expression profile in Xenopus embryos. 21 We showed that pdgf-b mRNA was not expressed in NCCs but in adjacent territories, indicating that pdgf-b could contribute to the early phases of NCC migration, given that these cells express, at least, pdgfr-α. In Xenopus, cranial NCCs migrate from the mesencephalic and rhombencephalic regions of the central nervous system (CNS) toward the branchial pouches, starting at late neurula stage (stage 19).…”
mentioning
confidence: 81%
“…For all these reasons, the role of pdgf‐b during embryonic life remains elusive and, so far, not fully understood. A new hint emerged from our recent analysis of the pdgf‐b gene‐expression profile in Xenopus embryos . We showed that pdgf‐b mRNA was not expressed in NCCs but in adjacent territories, indicating that pdgf‐b could contribute to the early phases of NCC migration, given that these cells express, at least, pdgfr‐α.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations